A Jabil Circuit Magyarország Kft. átfogó elemzése - Vass Barbara (2015)
In my thesis I have analyzed the financial situation of the Jabil Circuit Hungary Ltd. for the past 5 years. I have chosen this topic as in today’s world no company can live without analyzing its operations. Analysis is a tool, which provides information on the operation, profitability, efficiency and financial and economic situation of the company, therefore it has an effect on the activity of the company itself. In the first part of my thesis I made a literature review, which explains the importance of accounting, the role of financial statements in analysis, and explains the different types of reports. Later I give the detailed description of the analysis, I present their main types and their application methods. In the next section I write about the essence of the crisis, its stages, the crisis mana-gement methods, as in today’s world the companies are much concerned by this issue. The company manufactures and repairs electronic products, so in the fourth section I have tried to present the actual situation of the domestic electronics industry. In the fifth chapter I present the company’s history, the ownership structure, organizational structure, scope of activities, accounting policies and its vision. After that you can find the most important part of my thesis. The analysis was made with the indices that I have learned during the collage years. First I prepared a balance sheet analysis, which shows that the most important assets of the company are the working assets, within this, the raw materials. Furthermore it can be stated that the company has only short term liabilities. After the balance sheet analysis I have checked the financial situation of the company, from this it can be seen that the liquidity of the company is good. The working assets of the company do not cover the short term liabilities. Finally I have analyzed the profitability and efficiency of the company. Profitability of the company improved year after year. Efficiency of the assets, as well as the capital efficiency of the company improved in the recent years. Analyzing the cash flow of the company, it can be said that the capital resources are mainly from its business activities. It is a positive thing that the company developed its activities in the past five years, different investments were implemented, which can be seen in the negative investment cash flow.